A Study on Association of Nutritional Status and Life Style Habits in Children Aged 5-12 Years Having Emotional and Behavioral Disorder Attending Rural Tertiary Health Care Centre - S, Bhargavi; Prasad, K N Venkateshwara; B A, Murali Mohan (Journal of Neonatal Surgery, 2025)
Background: Emotional and behavioural disorders (EBD) in children are emerging public health challenges that can adversely affect mental, emotional, and social development. Nutritional status and lifestyle behaviours such as diet, physical activity, and sleep may influence mental health, especially in underserved populations. Objective: To assess the association between nutritional status and lifestyle habits among children aged 5–12 years diagnosed with EBD at a rural tertiary healthcare centre. Material and Methods: A cross-sectional study was conducted among 451 children attending the paediatric OPD at RL Jalappa Hospital from May 2023 to December 2024. Children were screened using the Child Symptom Inventory-4 (CSI-4), with 103 children identified with EBD undergoing further evaluation for nutritional and lifestyle parameters. Nutritional status was assessed using WHO growth standards, and lifestyle habits were recorded through structured interviews. Data were analysed using SPSS v22 with chi-square and Fisher’s exact tests. Results: Social anxiety (32%), generalized anxiety disorder (30.1%), and specific phobia (28.2%) were the most prevalent EBDs. Most children had normal nutritional status (70.9%) and adequate physical activity (93.2%). A significant association was found only between enuresis and undernutrition (p = 0.008). No significant associations were observed between other EBDs and breakfast skipping, activity levels, or sleep patterns. Conclusion: While most EBDs were not significantly associated with nutritional or lifestyle factors, undernutrition was linked to enuresis. The findings underscore the need for targeted screening and integrated approaches to paediatric mental health, especially in rural settings.